Analysis of lncRNA and mRNA Repertoires in Lung From BAFF-R-Deficient Pneumocystis-Infected Mice - Rong, Heng-Mo; Zhang, Chao; Rong, Guang-Sheng; Li, Ting; Qian, Xiao-Jun; Wang, Dong; Tong, Zhao-Hui (Frontiers in Immunology, 2022)
Background Pneumocystis pneumonia (PCP) is a common medical issue in immunosuppressive patients. Increasing evidence supports that B cells may play an essential role in PCP individuals. The present study aims to integrate lncRNA and mRNA expression profiles and further investigate the molecular function of mature B cells in PCP. Methods The lung tissue of wild-type (WT) mice and B-cell-activating factor receptor–deficient (mature B-cell deficiency, BAFF-R–/–) mice were harvested at 3 weeks after being infected with pneumocystis. After total RNAs were extracted, transcriptome profiling was performed following the Illumina HiSeq 3000 protocol. lncRNA-targeted miRNA pairs were predicted using the online databases. The Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) enrichment pathways were analyzed to functionally annotate these differentially expressed genes. Additionally, the immune-related lncRNA–miRNA–mRNA–ceRNA network was subsequently performed. The quantitative real-time PCR (RT-PCR) analysis was conducted to evaluate the lncRNA and mRNA expression profiles in WT-PCP mice and BAFF-R–/– PCP mice. Results Compared with the control group, 166 mRNAs were observed to be aberrantly expressed (fold change value ≥2; P <0.05) in the BAFF-R–/– PCP group, including 39 upregulated and 127 downregulated genes, while there were 69 lncRNAs differently expressed in the BAFF-R–/– PCP group, including 15 upregulated and 54 downregulated genes. In addition, GO and KEGG pathway analyses showed that BAFF-R deficiency played an important role in the primary and adaptive immune responses in PCP. Furthermore, the lncRNA and mRNA co-expression network was established. We noted that the core network of lncRNA-TF (transcription factor) pairs could be classified into the categories including infection and immunity pathways. Conclusion In summary, in this study, we further explored the role of mature B cells in the pathogenesis and progression of PCP and the data demonstrated that BAFF-R deficiency could play a significant role in immune regulation in the PCP population.